Rozwój przedsiębiorczości w Polsce w ujęciu międzywojewódzkim - Stańczyk, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The main purpose of the publication is to assess regional (inter-voivodeship) differences in the development of entrepreneurship in Poland in the light of the proposed set of indicators, calculated on the basis of statistical data collected by Statistics Poland. Bearing in mind the availability of empirical data, it was assumed that the level of entrepreneurship development can be demonstrated by the values of indicators characterizing three basic dimensions of entrepreneurship: propensity to start a business, innovative activity and financial results, including export activity. These dimensions were analyzed in terms of time — from Poland’ saccession to the European Union to 2018. During the analyzed period, financial indicators showed particularly dynamic characteristics (especially in the scope of export activity and gross financial result). At the same time, great diversity and a large degree of spatial concentration in terms of these characteristics were maintained. The relation of newly-registered entities to de-registered entities in most voivodships was increasing, which may indicate a growing tendency to start their own business and, indirectly, also to increase the survival of companies on the market. On the other hand, the propensity to invest in innovation in almost all voivodships decreased significantly over the years under study, while the large disproportion in terms of the amount of financial expenditure on innovation activities — the budget for innovation in enterprises — persisted among voivodships. On the other hand, the smallest degree of diversity across voivodships was recorded forthe percentage of innovative enterprises and the percentage of enterprises that incurred expenditure on innovation.
Keywords: entrepreneurship; innovation; REGON register; financial results of business entities